1994
DOI: 10.1089/aid.1994.10.1557
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of HTLV Type I in Japan: Evidence for Two Distinct Ancestral Lineages with a Particular Geographical Distribution

Abstract: Japan is one of the highest endemic areas of the world for human T cell leukemia-lymphoma virus type I (HTLV-I). To gain new insight as to the origin of this virus in Japan and especially in the southern islands of the archipelago, we investigated the long terminal repeat (LTR) of 67 newly isolated HTLV-I proviral DNAs from peripheral blood mononuclear cells of HTLV-I-infected individuals for their restriction fragment length polymorphism (RFLP). The specimens were from Japanese living in different geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…2). 13 Judging by the geographic closeness and historic interactions between Taiwan and Japan (Taiwan had been occupied by the Japanese between A.D. 1895 and 1945), it is logical to speculate that the predominant HTLV-I in Taiwan would also be group b (Japanese). On the contrary, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). 13 Judging by the geographic closeness and historic interactions between Taiwan and Japan (Taiwan had been occupied by the Japanese between A.D. 1895 and 1945), it is logical to speculate that the predominant HTLV-I in Taiwan would also be group b (Japanese). On the contrary, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In Cosmopolitan subtype A, TSP1 (Caribbean), 22 CRI (Caribbean), 23 CH (Caribbean), 24 DJ16 (Japan), 13 and AINU (Japan) 9 belong to group a; DJ9 (Japan), 13 ATK (Japan), 25 H5 (Japan), 26 and ATM (Japan) 27 belong to group b; 1010/3 (Caribbean) and HS35 (Caribbean) 28 belong to group c; and BO (Algeria) 29 and Pr144 (Morocco) 29 belong to group d. In addition, EL (Zaire), 9 MWMG (Zaire), 9 H24 (Cameroon), 8 and PH236 (Gabon) 8 belong to subtype B; MEL5 (Solomon Islands) 30 and H23 (Cameroon) 8 are subtype C and subtype D, respectively. MEL5 was used as the outgroup to transform unrooted trees to rooted trees.…”
Section: Nucleotide Sequence Accession Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult T cell leukemia (ATL), an aggressive T-cell malignancy without an effective cure (Yoshida et al, 1982), is found to be caused by human T-cell leukemia virus type I (HTLV-I) infection and occurs in HTLV-I-endemic areas, such as southwestern Japan, Central and South America, the Caribbean islands, Middle East, Aboriginal regions in Australia, and Intertropical Africa (Uchiyama et al, 1977;Vidal et al, 1994). The prognosis is poor, with less than 1 year survival for patients (Goncalves et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The cosmopolitan subtype is further divided into three subgroups: A, B, and C, which correspond to the Transcontinental subgroup, the Japanese subgroup, and the West African subgroup, respectively. The Transcontinental subgroup is widely distributed throughout South America, the Caribbean basin and Japan [Gallo et al, 1983;Ishida and Hinuma, 1986;Miura et al, 1994;Vidal et al, 1994]. Although this distribution pattern of HTLV-1 may reflect global population movements during the prehistoric period, as well as more recently, the origin of HTLV-1 in Japan is still hotly disputed [Suzuki and Gojobori, 1998;Verdonck et al, 2007].…”
Section: Introductionmentioning
confidence: 99%